Weapons effects modelling for safety applications. (15th May 2019) - Anderson, Graeme; Reed, David; Nucci, Simon Di; Kwong, Anthony; Wilson, Janet
Weapon effect modelling has many applications, but in this paper we focus on how advanced computer models can be used to assess the effectiveness of blast shielding structures and materials, for example to improve the safety of weapons production. Safety laws are changing from prescriptive, solution-based regulations to a risk-management-based approach, so being able to estimate the performance of protective measures allows us to produce directly-relevant safety evidence. Such an approach can be used to show that risks are reduced so far as is reasonably practicable (SFAIRP) in order to demonstrate compliance with the WHS Act, 2011. This paper first describes how a variety of computer-based models for the prediction of the development and propagation of blast pressures can be used to provide a detailed assessment of the risks associated with explosions in complex environments, with particular reference to injury assessment - something that is sometimes impractical with simpler techniques. We then show how some of these techniques have been used in two real-world examples to successfully support safety case development. Finally, we extrapolate from the examples, showing how these techniques could be applied to assess weapons safety in different environments, or for risk assessment in defensive or offensive scenarios.